PRINSIP KEWAJARAN DAN PERTANGGUNGJAWABAN DALAM GOOD CORPORATE GOVERNANCE BUMN: ANALISIS LITERATUR TENTANG PERANANNYA DALAM MEWUJUDKAN KEADILAN PEMANGKU KEPENTINGAN DAN MENINGKATKAN DAYA SAING PERUSAHAAN - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2026)
This study analyses the role of the principles of fairness and responsibility in Good Corporate Governance (GCG) of state-owned enterprises through a systematic literature review, focusing on their contribution to stakeholder fairness and increased corporate competitiveness. The results show that the principle of fairness ensures proportional distribution of benefits and protection of minority rights through inclusive decision-making mechanisms, while responsibility strengthens social legitimacy through transparent reporting and regulatory compliance with KNKG and OECD standards. Simultaneously, these two principles reduce the risk premium by 20-30%, facilitate access to global capital markets via IFRS, and enhance the operational efficiency and competitive reputation of SOEs in the international arena. The main findings confirm the synergy between fairness and responsibility, creating a virtuous cycle between stakeholder fairness (distributive, procedural, interactional) and competitive advantage through dynamic capabilities, corporate reputation, and managerial meritocracy. Implementation gaps have been identified in political intervention and the lack of an ethical organisational culture, which hinders the transformation of SOEs into world-class corporations.